Automated calculation of pressure losses in volumetric hydraulic drive - I. M. Murseev; Y. I. Privalovа (Вестник СибАДИ, 2017)
Computer aided design is the process by which all or part of the design solutions obtained using computer technology. One of the main model of computer aided design problems is to calculate or univariate analysis. This paper describes how the authors developed the software package "The Calculation of pressure losses in the hydraulic lines of the hydraulic drive of volumetric" in the programming environment Visual Basic. On the basis of the implemented application improves a number of works on calculation and design of a volumetric hydraulic actuator, and the computational experiment based on real technical data.